Diet cost plays a key role in determining the risk of pediatric attention deficit hyperactivity disorder: Findings from a case–control study. Issue 12 (9th August 2022) - Abbasi, Khadijeh; Foshati, Sahar; Mehrabani, Sanaz; Ghiasvand, Reza; Bagherniya, Mohammad; Rouhani, Mohammad Hossein
Abstract: The aim of our study was to assess the association between diet cost and attention deficit hyperactivity disorder (ADHD) in children. This study was a case–control study conducted in Isfahan, Iran. Based on the Diagnostic and Statistical Manual of Mental Disorders‐V criteria, a total of 200 children aged 4–12 years with ADHD and 300 age‐ and sex‐matched children without ADHD, respectively, participated in case and control groups. A validated food frequency questionnaire that contained 168 food items was used to assess the dietary intake. The cost of food items was obtained from licensed markets. The food price was corrected for edible portion sizes as well as food weight changes due to cooking process. Our results indicated that diet cost per 1000 kcal was significantly lower in the case group compared with the control group (60, 843.48 ± 6987.83 vs. 67, 828.33 ± 8989.48 Rials, p  < .01). In the crude model, a significantly lower risk of ADHD was observed in the higher quartiles of diet cost per 1000 kcal (odds ratio (OR) = 0.06; 95% confidence interval (CI) = 0.03, 0.13; p  < .001). This finding remained significant, even after adjustment for potential confounders such as age, gender, body mass index (BMI), socioeconomic status (SES), and intakes of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and saturated fatty acids (SFA). Therefore, it seems that the risk of ADHD is inversely associated with diet cost in children. Further studies, particularly longitudinal ones, are warranted. Abstract : Diet cost was lower in the case group than in the control group.An inverse association was found between diet cost and the risk of ADHD in children.